(untitled) (Серія: Історія. Політологія, 2024)
The article examines the influence and phenomenon of a storytelling, as a tool of citizen diplomacy, on the development of modern full-scale Ukrainian diplomacy. Based on the assumption about the significant influence of personal stories on the shaping of public opinion, the study was aimed to empirically confirm the relationship between citizen diplomacy, which often uses storytelling tools, and the perception of russian aggression against Ukraine by the European Union’s citizens. It is assumed, that in the conditions of the modern information warfare, the influence of such stories on the formation and developing of international solidarity is an effective mechanism of citizen diplomacy. To achieve the main goal of the study, a survey was conducted among citizens of certain European Union countries in order to identify their readiness to accept Ukrainian narratives.